The rise and fall of network computers. - Lee, Ernie Poh Khoon. (2008)
"The network is the computer." This is an aphorism used by Sun Microsystems, which together with Oracle Corporation, introduced the concept of Network Computing to the computing world in 1996. They even proudly proclaimed network computers (NCs) to be the Personal Computer (PC) killer. But there are also many analysts who are skeptical about the new concept and this has caused the adoption of NCs to be slower than anticipated.To date, it seems tha tplans for a widespread adoption of NCs have flopped. The main objective of our research is to trace the rise and fall of the idea of NCs using the Product Life cycle as our theoretical framwork.